ANALISIS PENGARUH ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) PERFORMANCE TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Bahdin Nur Tanjung; Parlaban Karo-Karo; Resi Lasmaria Naibaho (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on firm value of companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. The research is motivated by the Financial Services Authority of Indonesia (OJK) regulations on sustainability reporting, which encourage the integration of ESG into business practices. However, prior studies in emerging markets show mixed and limited evidence, particularly for the Indonesian context. The study aims to measure ESG performance levels, test the impact of ESG on firm value, and analyze whether the effect differs between high-environmental-impact and low-environmental-impact sectors. In addition, it investigates the moderating role of corporate governance and evaluates the relative contribution of each ESG dimension. The theoretical framework includes stakeholder theory, resource-based view, legitimacy theory, and signaling theory. The research employs panel data regression analysis using both cross-sectional and time-series data. The findings are expected to contribute to more sustainable business practices in Indonesia.